Mechanosynthesis of Eutectics of Anti‐Inflammatory Drug Ethenzamide – A Comparison with Analogous Cocrystals. Issue 9 (22nd June 2021) - Rajbongshi, Trishna; Kumar Sarmah, Kashyap; Ganduri, Ramesh; Cherukuvada, Suryanarayan; Arhangelskis, Mihails; Thakuria, Ranjit
Abstract: Mechanochemical milling of ethenzamide (ETZ), a nonsteroidal anti‐inflammatory drug, with substituted aromatic carboxylic acids as well as anti‐tuberculosis drug pyrazinamide (PZA) resulted in the formation of eutectics. Although a large number of cocrystals as well as polymorphic cocrystals are reported for ETZ, for the first time we have synthesized six eutectics including an instance of a drug‐drug eutectic system. Supramolecular synthon energy calculations validate the formation of eutectic mixtures over cocrystals with coformers considered in our study. Abstract : Mechanochemistry can be used to prepare eutectic systems similar to that known for cocrystals. Supramolecular synthon energy calculations validated the formation of eutectics over cocrystals with the coformers considered in our study.